Three lines of defense: A multifunctional coating with anti-adhesion, bacteria-killing and anti-quorum sensing properties for preventing biofilm formation of Pseudomonas aeruginosa. (1st October 2022) - Zou, Yi; Liu, Chunxia; Zhang, Haixin; Wu, Yan; Lin, Yuancheng; Cheng, Jingjing; Lu, Kunyan; Li, Luohuizi; Zhang, Yanxia; Chen, Hong; Yu, Qian
Abstract: Surfaces of synthetic materials are highly susceptible to pathogenic bacteria colonization and further biofilm formation, leading to device failure in both biomedical and industrial applications. Complete elimination of the mature biofilms formed on the surfaces, however, remains a great challenge due to the complexity of chemical composition and physical structure. Therefore, prevention of biofilm formation becomes a preferred strategy for solving the biofilm-associated problems. Herein, a multifunctional coating showing three lines of defense to prevent biofilm formation of Pseudomonas aeruginosa is fabricated by a simple and versatile method. This coating is composed of multilayers of quaternized chitosan with bactericidal property and acylase with anti-quorum sensing property and a topmost layer of hyaluronic acid with anti-adhesion property. The substrate deposited with this coating could suppress initial adhesion of a majority of bacteria, and then kill the attached bacteria and interfere with their quorum sensing systems related to biofilm formation. The results of short-term antibacterial experiments show that our coating reduced 98 ± 2% of attached live bacteria. In long-term antibiofilm experiments, this "three lines of defense" design endows the coating with enhanced antibiofilm property against the biofilm formation for at least 3 days by reducing 98 ± 1% of bacterial proliferation and 71 ± 2% of biomass production. Benefiting from the natural building blocks with good biocompatibility and the versatile and environmentally friendly preparation method, this coating shows negligible cytotoxicity and broad applicability, providing great potential for a variety of biomedical applications. Statement of significance: Pathogenic biofilms formed on the surfaces of medical devices and materials pose an urgent problem, and it remains challenging to treat and eradicate the established biofilms. Herein, we developed an antibiofilm coating showing three lines of defense to prevent biofilm formation, which could be deposited on diverse substrates via a simple and versatile method. This coating was based on three natural materials with anti-adhesive, bactericidal, and anti-quorum sensing properties and showed different function in a self-adaptive way to target the sequential stages of biofilm formation by preventing initial bacterial adhesion, killing attached bacteria and interfering with their quorum sensing system to inhibit bacterial proliferation and biofilm maturation. This coating with improved antibiofilm performance might provide a simple and reliable solution to the problems associated with biofilm on surfaces. Graphical abstract: Image, graphical abstract